2015
DOI: 10.1123/jsr.2014-0195
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Using a Handheld Tablet and Application to Measure Lower-Extremity Alignment Angles

Abstract: A handheld tablet and app is promising for evaluating landing kinematics and identifying individuals at risk for knee injury in a clinical setting. Intertrial reliability is good to excellent when using average trial measures. Interrater reliability is fair to excellent depending on experience level. Multiple trials should be assessed by a single rater when assessing lower-extremity mechanics with a handheld tablet and app, and results may vary with experience level or training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…Our findings show that initial contact angles for both limbs can be reliably measured using 2D video analysis, with ICCs ranging from 0.87-0.93 and CV% between 1.0-1.6% across all drop heights (Table 1-3). Previously, SEM values for establishing sagittal-plane knee and hip angles at initial contact using 2D analysis during drop jumps have shown to range between 1.4-4.1˚ and 1.2-1.3˚, respectively (King & Belyea, 2015). These values are similar to our own findings (Table 1-3).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings show that initial contact angles for both limbs can be reliably measured using 2D video analysis, with ICCs ranging from 0.87-0.93 and CV% between 1.0-1.6% across all drop heights (Table 1-3). Previously, SEM values for establishing sagittal-plane knee and hip angles at initial contact using 2D analysis during drop jumps have shown to range between 1.4-4.1˚ and 1.2-1.3˚, respectively (King & Belyea, 2015). These values are similar to our own findings (Table 1-3).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, FPPA provides a reliable representation of knee valgus/varus angle in the deepest landing position (Dingenen, Malfait, Vanrenterghem, Verschueren, & Staes, 2014;McLean et al, 2005;Mizner, Chmielewski, Toepke, & Tofte, 2012;Munro et al, 2012) and is a valid measure of frontalplane knee mechanics during landings when compared to 3D analysis. However, for joint angle measurements in the sagittal-plane, only Dingenen et al (2015) and King and Belyea (2015) have investigated the reliability of 2D analysis for measurements of bilateral landing activities. In all of these investigations, only peak angles for the hip, knee and ankle joints were measured.…”
Section: Introductionmentioning
confidence: 99%
“…The excellent intrarater and interrater reliability found in this study was similar to that reported in other studies using healthy populations. 4,5,9 The interrater reliability of the existing literature ranged from moderate to excellent, with King and Belyea 8 reported .45 to .99 during a drop jump task, whereas Herrington and Munro 7 reported .97 to 1.0 in a single-leg landing and Mizner et al 9 reported .89 during a drop vertical jump. In terms of intrarater reliability, Herrington and Munro 7 reported .58 to .96 in a single-leg landing, whereas Mizner et al 9 reported .95 during drop vertical jump and Maykut et al 4 reported .96 to .98 during running.…”
Section: Discussionmentioning
confidence: 98%
“…Knee valgus was determined using the frontal plane projection angle formed by a line along the midline of the thigh to the center of the patella and a line from the center of the patella to a point bisecting the malleoli (Figure 1). 4,7,8 The investigator visually determined the time point of peak knee valgus for measurements.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation